2022
DOI: 10.1183/23120541.00530-2022
|View full text |Cite
|
Sign up to set email alerts
|

Is being able to walk to the letterbox life-changing? A qualitative assessment of measures of improvement in persistent breathlessness

Abstract: This manuscript has recently been accepted for publication in the ERJ Open Research. It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJOR online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The most recent RCT of regular, low-dose ER morphine in COPD, the BEAMS (Breathlessness, Exertion, And Morphine Sulfate) trial, including 156 participants, did not show an improvement in their primary outcome, worst breathlessness after 1 week of treatment, or in other outcomes 19▪▪ . However, an exploratory analysis of qualitative and quantitative data from this study suggested that there are so-called ‘super-responders’ among the participants 26 . These participants described the intervention as life-changing, reported easier breathing, better sleep, improved ability to walk, being able to do meaningful activities, and higher well-being.…”
Section: Pro: Opioids Should Be Used For Breathlessness In Serious Di...mentioning
confidence: 83%
See 1 more Smart Citation
“…The most recent RCT of regular, low-dose ER morphine in COPD, the BEAMS (Breathlessness, Exertion, And Morphine Sulfate) trial, including 156 participants, did not show an improvement in their primary outcome, worst breathlessness after 1 week of treatment, or in other outcomes 19▪▪ . However, an exploratory analysis of qualitative and quantitative data from this study suggested that there are so-called ‘super-responders’ among the participants 26 . These participants described the intervention as life-changing, reported easier breathing, better sleep, improved ability to walk, being able to do meaningful activities, and higher well-being.…”
Section: Pro: Opioids Should Be Used For Breathlessness In Serious Di...mentioning
confidence: 83%
“…Their quantitative data showed improvement in dyspnea scores, active minutes, and active calories used, which remained after 6 months of morphine use. These findings suggest that meaningful outcomes for patients, such as perceived improvement in meaningful activities and sleep, are not reflected by the traditional outcome measures of currently available RCTs 26 . However, it should be noted that this was a secondary, exploratory analysis without a randomized comparison group.…”
Section: Pro: Opioids Should Be Used For Breathlessness In Serious Di...mentioning
confidence: 93%